2000
DOI: 10.1002/1097-4628(20001010)78:2<338::aid-app140>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal bulk crystallization and subsequent melting behavior of syndiotactic polypropylenes: Crystallization from the melt state

Abstract: Various macrokinetic models, namely, the Avrami, the Tobin, and the Ozawa models, were applied to describe the crystallization process of syndiotactic polypropylene (s-PP) under nonisothermal conditions. Both Avrami and Tobin models were shown to provide a fair description of the experimental data. The Avrami exponent n a was found to range from 2.4 to 5.3, while the Tobin exponent n t was found to range from 3.1 to 6.7. The Ozawa model was found to describe the nonisothermal crystallization kinetics of s-PP v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
5
25
1
Order By: Relevance
“…The Avrami exponents (n) and the corresponding correlation (r 2 ) of the plots at various temperatures of the blend samples are summarized in Table 2. The n values increased with increasing of the temperatures, as previously reported about the crystallization of sPP [44]. The large n values of Bl-75 should be caused by the slow crystallization of sPP in the blend samples.…”
Section: Crystallization Of Spp In the Blend For Short Periodsupporting
confidence: 79%
See 2 more Smart Citations
“…The Avrami exponents (n) and the corresponding correlation (r 2 ) of the plots at various temperatures of the blend samples are summarized in Table 2. The n values increased with increasing of the temperatures, as previously reported about the crystallization of sPP [44]. The large n values of Bl-75 should be caused by the slow crystallization of sPP in the blend samples.…”
Section: Crystallization Of Spp In the Blend For Short Periodsupporting
confidence: 79%
“…The T c s of the blend samples detected on all the cooling rates are summarized in Table 1. The T c s of sPP in the blend samples decreased with increasing the cooling rate, as previously repoted about the neat sPP [44]. Bl-50, Bl-75, and Bl-90 showed lower T c s than that of the neat sPP.…”
Section: Crystallization Of Spp In the Blend For Short Periodsupporting
confidence: 77%
See 1 more Smart Citation
“…cooling rates). However, this problem has largely been avoided by dropping off the minus sign in the negative heating rates [23].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Both quiescent isothermal and non-isothermal melt-crystallization studies revealed that sPP is a slowly crystallizing polymer. [10,11] The addition of nucleating agents may help enhance the crystallization rates by Summary: The effects of various nucleating agents [e.g. 1,3:2,4-dibenzylidene sorbitol (DBS), 1,3:2,4-di-p-methyldibenzilidene sorbitol (MDBS), 1,3:2,4-di-m,p-methylbenzylidene sorbitol (DMDBS), kaolin, talcum, marl, titanium dioxide (TiO 2 ) and silica (SiO 2 )] on non-isothermal melt crystallization and the subsequent melting behavior and mechanical properties of nucleated syndiotactic poly(propylene) (sPP) in comparison with those of the neat sample were investigated.…”
Section: Introductionmentioning
confidence: 99%